The prospects of hard spring wheat cultivation to ensure internal consumption - Barabolia, O.; Latysh А. (Scientific Progress & Innovations, 2024)
Under modern conditions, the Ukrainian farmers have the aim to manufacture high-quality, competitive and safe agricultural products for satisfying the internal market. An important direction in it is the cultivation of high-quality hard spring wheat, which occupies a significant place in food supply not only in Ukraine, but also in the world community, making about 5–7 % of all the world areas under wheat cultivation. The purpose of the article is to study the prospects of developing the internal market of hard spring wheat production and consumption. High grain quality and yield capacity are important indicators assisting in the increase in the volumes of this crop cultivation for internal requirements. The main directions of grain use were determined – manufacturing grits and high-quality pasta products, which require flour containing 25–26 % of gluten. Unsatisfactory quality of domestic hard spring wheat grain leads to the increase in the import of manufactured pasta products from hard wheat varieties or high-quality flour for the domestic production. To solve the problem of raising the yield capacity and quality of hard spring wheat grain, it is recommended to apply modern recognized varieties, follow the technology of cultivating and introducing the promising methods of pre-sowing seed treatment, plant growth stimulants, ecological methods and technologies. As a result, the Ukrainian manufacturers of pasta products and grits will receive the necessary raw materials, which will be cheaper than the imported and will make the price for ready-made products lower. As hard wheat grain is twice as expensive as soft varieties’ grain, this will make farms profitable under the limited grain export and the constant price growth for fuel and fertilizers. The cooperation of farmers with the manufacturers of ready-made products to develop the necessary infrastructure (for example, a mill) and the use of modern logistic centers (dry ports) are important factors in the improvement of this direction in crop growing.